THE USE OF WORD SEARCH PUZZLES TO IMPROVESTUDENTS' VOCABULARY - Mustika, Yeni; Dashela , Tarina (Jurnal Ilmiah Spectral, 2023)
This research purposed to describe the students' improvement in vocabulary by using word search puzzles. This was classroom action research with two cycles conducted on the first semester students of Bina Sarana Informatika Pontianak University consisting of 40 students. This was the classroom action research. Planning, acting, observing, and reflecting were conducted in each cycle. Field notes, observation checklists, interviews, and individual tests were used as the tools to collect the data. Qualitative and quantitative analysis would be used to analyze the data. The finding of this research showed that the use of word search puzzles could build the students' motivation and decrease students' reluctance to find a new vocabulary. It also experienced students to identify the word which allowed the students to have a better understanding of vocabulary. The word search puzzle led the students to build brains by finding the hidden word and improving vocabulary mastery. It was an effective way for the teacher in teaching vocabulary.